188k views
1 vote
2x +3y = 9
-3x +3y = -6

User Mtszkw
by
5.3k points

1 Answer

9 votes

Rewrite the second equation:

This is to make the calculation easier. There are other ways to do this as well.

3y = 3x - 6

Substitute that into the first equation:

Since they are the same thing (=), it is possible to replace 3y.

2x + (3x - 6) = 9

Solve the equation:

2x + 3x = 9 + 6

5x = 15

x = 3

Substitute x = 3 into the first equation:

2(3) + 3y = 9

6 + 3y = 9

3y = 3

y = 1

Answer: x = 3, y = 1

User Ethan G
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.